The essential characteristics of future experts for the professional selfdevelopment - Frytsiuk, V. A. (Problems of Engineer-Pedagogical Education, 2018)
In the context of modernization of higher education, one of the factors in providing the state competitiveness on the global level is to improve specialists’ preparation quality, in particular, to form prospective teachers’ motivation to continuous professional education and professional selfdevelopment. Self-development of personality of prospective teacher is urgent to the modern educational process. Self-development – is mental or physical man’s development which he achieves by own unaided study, exercises. Self-development is carried out by own forces, without the influence or assistance of any external forces. Self-development is considered as person’s comprehension of individual qualities and their enrichment through inclusion in appropriate activities, including educational one. Analysis of contemporary psychological and educational research confirmed that in the scientific psychological and pedagogical literature the term «teacher’s self-development» has no clear consistent definition due to different methodological approaches to its consideration. The process of professional self-development of future professionals and structure are considered by scientists from the standpoint of different approaches.